Food Security Status and Coping Strategies Among Adolescents During the Covid-19 Pandemic in Mamuju - Nurbaya Nurbaya; Najdah Najdah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Adolescents are one of the vulnerable groups experiencing nutritional problems during the Covid-19 pandemic. Food insecurity in adolescents also impacts access to food, mental disorders, and eating disorders (eating disorders), which can cause nutritional problems in adolescents. This study aimed to measure the food security status of adolescents during the Covid-19 pandemic. Data was collected using a qualitative method through in-depth interviews and focus group discussions (FGD). The informants were state high school/vocational school students aged 15-17 amount 36 people who were selected by purposive sampling in the Mamuju District area, Mamuju Regency, in March-November 2021. Adolescents were vulnerable to experiencing food insecurity during the Covid-19 pandemic. This study found that adolescents experienced food insecurity during the Covid-19 pandemic, ranging from mild food insecurity (30.6%), moderate (58.6) to severe (1.8). Only 9% of youth experience good food security. As conclusion that adolescents experienced food insecurity status and doing several coping strategies to overcome this food insecurity problem by helping their parents to sell goods and find additional jobs outside the home during the Covid-19 pandemic. The problem of food insecurity will indirectly affect the nutritional status of adolescents.